2019
DOI: 10.1002/jmv.25564
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of HIV‐1 integrase strand‐transfer inhibitors against mutants with integrase resistance‐associated mutations and their frequency in treatment‐naïve individuals

Abstract: The development of resistance to human immunodeficiency virus 1 (HIV‐1) integrase strand‐transfer inhibitors (INSTI) has been documented; however, knowledge of the impact of pre‐existing integrase (IN) mutations on INSTI resistance (INSTI‐R) is still evolving. The frequency of HIV‐1 IN mutations in 2177 treatment‐naïve subjects was investigated, along with the INSTI susceptibility of site‐directed mutant viruses containing major and minor INSTI‐R mutations. Total 6 of 39 minor INSTI‐R mutations (M50I, S119P/G/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 29 publications
(57 reference statements)
2
27
0
Order By: Relevance
“…Five highly polymorphic mutations, R20K [ 50 ], I72V [ 9 , 33 , 51 ], L74I [ 7 , 23 , 24 , 25 , 26 ], S119P [ 51 , 52 ], and V201I [ 11 , 26 , 38 , 53 ], were frequently reported in regard to a small reduction in replication capacity relative to the wild type. It has been reported that in the absence of major mutations, all these polymorphic mutations had little, if any, effect on drug susceptibility in vitro, thus suggesting a secondary role for viral fitness rescue and increasing resistance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five highly polymorphic mutations, R20K [ 50 ], I72V [ 9 , 33 , 51 ], L74I [ 7 , 23 , 24 , 25 , 26 ], S119P [ 51 , 52 ], and V201I [ 11 , 26 , 38 , 53 ], were frequently reported in regard to a small reduction in replication capacity relative to the wild type. It has been reported that in the absence of major mutations, all these polymorphic mutations had little, if any, effect on drug susceptibility in vitro, thus suggesting a secondary role for viral fitness rescue and increasing resistance.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 108 mutations were detected, including 16 highly polymorphic mutations. Five of them (R20K, I72V, L74I, S119P, and V201I) were described as INSTI resistant [7,9,11,[23][24][25][26]33,36,[49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, the amine portion of the scaffold was modified to substitute an oxadiazole group for the oxalamide, producing RAL [53]. As stated above, RAL potently inhibited IN strand transfer in both in vitro assays (IC 50 ) and had antiviral activity against HIV-1 in single round replication assays (EC 50 ) [53,74,75]. RAL was also broadly active against a number of HIV-1 isolates, human immunodeficiency virus type two (HIV-2), and SIV [76].…”
Section: Raltegravir (Ral)mentioning
confidence: 99%
“…When the amino acid substitutions Y143R, N155H, and G140S/Q148H were introduced in HIV-1 pNL4-3 and the EC 50 values of the WT and mutant viruses were determined using single round replication assays, the IN mutants Y143R and N155H caused substantial losses in potency (for Y143R, the fold change (FC), which is the decrease in potency between WT and IN mutant, was 41, and for N155H, the FC was 38). RAL displayed an even larger loss in potency with the IN double mutant G140S/Q148H (the FC was 475) [75]. Mutations in the three amino acid substitution pathways arise at different rates [81,[83][84][85].…”
Section: Raltegravir (Ral)mentioning
confidence: 99%
“…To gain insight into the mechanisms of drug resistance, we additionally determined the structure of BIC bound to IN mutant Q148H/G140S intasomes. The double mutation, which arose initially in response to RAL treatment [29], was subsequently shown to confer significant (> 150-fold) cross-resistance to EVG, yet overall milder, approximately twofold to 10-fold, resistance to DTG and BIC [7,[30][31][32][33].…”
Section: Insights Into Insti Drug Resistance Mechanismsmentioning
confidence: 99%